Statin treatment and muscle symptoms: series of randomised, placebo controlled n-of-1 trials. (24th February 2021) - Herrett, Emily; Williamson, Elizabeth; Brack, Kieran; Beaumont, Danielle; Perkins, Alexander; Thayne, Andrew; Shakur-Still, Haleema; Roberts, Ian; Prowse, Danielle; Goldacre, Ben; van Staa, Tjeerd; MacDonald, Thomas M; et al.
Abstract: Objective: To establish the effect of statins on muscle symptoms in people who had previously reported muscle symptoms when taking statins. Design: Series of randomised, placebo controlled n-of-1 trials. Setting: Primary care across 50 sites in the United Kingdom, December 2016 to April 2018. Participants: 200 participants who had recently stopped or were considering stopping treatment with statins because of muscle symptoms. Interventions: Participants were randomised to a sequence of six double blinded treatment periods (two months each) of atorvastatin 20 mg daily or placebo. Main outcome measures: At the end of each treatment period, participants rated their muscle symptoms on a visual analogue scale (0-10). The primary analysis compared symptom scores in the statin and placebo periods. Results: 151 participants provided symptoms scores for at least one statin period and one placebo period and were included in the primary analysis. Overall, no difference in muscle symptom scores was found between the statin and placebo periods (mean difference statin minus placebo −0.11, 95% confidence interval −0.36 to 0.14; P=0.40)). Withdrawals because of intolerable muscle symptoms were 18 participants (9%) during a statin period and 13 (7%) during a placebo period. Two thirds of those completing the trial reported restarting long term treatment with statins. Conclusions: No overall effect of atorvastatin 20 mg on muscle symptoms compared with placebo was found in participants who had previously reported severe muscle symptoms when taking statins. Most people completing the trial intended to restart treatment with statins. N-of-1 trials can assess drug effects at the group level and guide individual treatment. Trial registration: ISRCTN30952488, EUDRACT 2016-000141-31, NCT02781064 .